Surface Microstructure of Nanoaluminized CoCrAlY Coating Irradiated by HCPEB. (5th May 2016) - Han, Zhiyong; Han, Jian; Jing, Zhenzhu
Abstract : A thermal sprayed CoCrAlY coating was prepared by air plasma spray on the surface of Ni-based superalloy GH4169; then, a nanoscale aluminum film was deposited with electron beam vacuum deposition on it. The coatings irradiated by high-current pulsed electron beam were investigated. After HCPEB treatment, the Al film was remelted into the bond coat. XRD result shows that Al and Al2 O3 phase were recorded in the irradiated and aluminized coatings, while Co-based oxides which originally existed in the initial samples disappeared. Microstructure observations reveal that the original coating with porosity, cavities, and inclusions was significantly changed after HCPEB treatment as compact appearance of interconnected bulged nodules. Moreover, the grains on the irradiated coating were very refined and homogeneously dispersed on the surface, which could effectively inhibit the corrosive gases and improve the coating oxidation resistance.